PERILAKU ATTENTION DEFICIT HYPERACTIVITY DISORDER (ADHD) DALAM PROSES PEMBELAJARAN (STUDI KASUS PESERTA DIDIK) DI KELAS IV SD NEGERI GEJAYAN - Wakhaj, Nugrahini Indra Umratun; Rofiah, Nurul Hidayati (universitas Ahmad Dahlan, 2018)
The behavior of primary school-age students today is very diverse, one of these behaviors are children who are very difficult to manage, can not be silent and as if not paying attention to the lessons in the classroom. These children usually experience emotional and behavioral disorders in its development of ADHD (Attention Deficit Hyperactivity Disorder). This study aims to describe the behavior and impact of Attention Deficit Hyperactivity Disorder (ADHD) in the learning process in grade 4 students of SD Negeri Gejayan.This type of research is a type of Descriptive Qualitative research, with data collection techniques of observation, interview, and doumentation. The subjects in this research are DA fourth graders of SD Negeri Gejayan. While the data analysis techniques using data reduction, data presentation, and conclusions.The results showed that there was Attention Deficit Hyperactivity Disorder (ADHD) behavior in the learning process in Grade IV of Gejayan State Elementary School which consisted of three behaviors: inattensi, hyperactive and impulsive behavior. The impact of Attention Deficit Hyperactivity Disorder (ADHD) behavior affects three aspects including (1) impact on learning process or education, (2) impact on student's behavior in learning process and, (3) impact to social aspect of student in process learning.